Dietary Glucose Increases Glucose Absorption and Lipid Deposition via SGLT1/2 Signaling and Acetylated ChREBP in the Intestine and Isolated Intestinal Epithelial Cells of Yellow Catfish. Issue 7 (29th May 2020) - Zhao, Tao; Yang, Shui-Bo; Chen, Guang-Hui; Xu, Yi-Huan; Xu, Yi-Chuang; Luo, Zhi
ABSTRACT: Background: Dietary carbohydrate affects intestinal glucose absorption and lipid deposition, but the underlying mechanisms are unknown. Objectives: We used yellow catfish and their isolated intestinal epithelial cells (IECs) to test the hypothesis that sodium/glucose cotransporters (SGLTs) 1/2 and acetylated carbohydrate response element binding protein (ChREBP) mediated glucose-induced changes in glucose absorption and lipid metabolism. Methods: Yellow catfish (mean ± SEM weight: 4.68 ± 0.02 g, 3 mo old, mixed sex) were fed diets containing 250 g carbohydrates/kg from glucose (G, control), corn starch (CS), sucrose (S), potato starch (PS), or dextrin (D) for 10 wk. IECs were isolated from different yellow catfish and incubated for 24 h in a control or glucose (15 mM) solution with or without a 2-h pretreatment with an inhibitor [sotagliflozin (LX-4211) or tubastatin A (TBSA)]. Human embryonic kidney cells (HEK293T cells) were transfected with a Flag-ChREBP plasmid to explore ChREBP acetylation. Triglyceride (TG) and glucose concentrations and enzymatic activities were measured in the intestine and IECs of yellow catfish. They also were subjected to immunofluorescence, immunoprecipitation, qPCR, and immunoblotting. Immunoblotting and immunoprecipitation were performed with HEK293T cells. Results: The G group had greater intestine TGs (0.99- to 2.30-fold); activities of glucose 6-phospate dehydrogenase, 6-phosphogluconate dehydrogenase, and isocitrate dehydrogenase (0.12- to 2.10-fold); and expression of lipogenic genes (0.32- to 2.34-fold) than the CS,  PS,  and D groups. The G group had greater intestine sglt1/2 mRNA and protein expression than the CS, S and D groups (0.35- to 1.12-fold and 0.40- to 4.67-fold, respectively), but lower mRNA amounts of lipolytic genes (48.6%–65.8%) than the CS and PS groups. LX-4211 alleviated the glucose-induced increase in sglt1/2 mRNA (38.2%–47.4%) and SGLT1 protein (48.0%) expression, TGs (29.3%), and lipogenic enzyme activities (27.7%–42.1%) and gene expression (38.0%–55.5%) in the IECs. TBSA promoted the glucose-induced increase in TGs (11.3%), fatty acid synthase activity (32.6%), and lipogenic gene expression (21.6%–34.4%) in the IECs and acetylated ChREBP (10.5%) in HEK293T cells. Conclusions: SGLT1/2 signaling and acetylated ChREBP mediated glucose-induced changes in glucose absorption and lipid metabolism in the intestine and IECs of yellow catfish.